2012
DOI: 10.1089/dna.2011.1299
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation and Induction of Strand Breaks by Adriamycin and Daunomycin: A Study with Human Genomic DNA

Abstract: The anticancer drugs Adriamycin (ADR) and Daunomycin (DNM) of the anthracycline family are effective in treating a variety of cancers. Although their interactions with other cellular targets may play a role in the selective cytotoxicity of these drugs, it is generally believed that intercalation with DNA is essential for their activity. However, a relationship has not yet been established between intercalation and cellular processes leading to cytotoxicity. The present study was designed to investigate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…Binding to normal genomic DNA is reported (Ghosh et al, 2012) to remarkably quench the fluorescence of these drugs. Similar binding to mutated DNA isolated from K562 cells also resulted in quenching of the fluorescence of these drugs, eventually leading to saturation (figure not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Binding to normal genomic DNA is reported (Ghosh et al, 2012) to remarkably quench the fluorescence of these drugs. Similar binding to mutated DNA isolated from K562 cells also resulted in quenching of the fluorescence of these drugs, eventually leading to saturation (figure not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Previous binding studies of ADR and DNM with normal human genomic DNA isolated from peripheral blood showed preferred binding with DNM over ADR. These drugs also showed higher genotoxicity to normal lymphocytes (Ghosh et al, 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
See 2 more Smart Citations
“…The cytotoxic action of ADM has been explained by its intercalation into DNA [4], which results in inhibition of replication, transcription, and ultimately, translation. The free radicals generated by ADM participate in causing the DNA damage, lipid peroxidation and mitochondrial dysfunctions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%